Oxide-based solid electrolytes and all-solid-state lithium-ion batteries
Patent Information
- Application Number
- JP2022025006
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-02-21
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-02-21
AI Technical Summary
【0014】 本発明によれば、良好なイオン伝導度を有する酸化物系固体電解質、及び、それを用いた全固体リチウムイオン電池を提供することができる。
Smart Images

Figure 0007648559000002 
Figure 0007648559000003 
Figure 0007648559000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an oxide-based solid electrolyte and an all-solid-state lithium-ion battery. [Background technology]
[0002] In recent years, with the rapid spread of information-related devices and communication devices such as personal computers, video cameras, and mobile phones, the development of batteries to be used as power sources for these devices has become important. Among these batteries, lithium ion batteries have attracted attention from the viewpoint of their high energy density. In addition, there is a demand for improvements in the energy density and battery characteristics of lithium secondary batteries for large-scale applications such as vehicle-mounted power sources and load leveling.
[0003] LISICON-type oxide-based solid electrolytes are expected to be the next-generation solid electrolyte for all-solid-state batteries as solid materials that conduct Li ions. In addition, it is possible to introduce Li deficiency or excess Li by replacing it with ions of different valence, and it has the advantage that materials can be prepared by combining various elements.
[0004] In addition, in order to improve the characteristics of all-solid-state lithium-ion batteries, solid electrolytes with high ionic conductivity are required. Non-Patent Document 1 discloses a technology aimed at improving the ionic conductivity in LISICON-type oxide-based solid electrolytes. [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] Guowei zhao et al., Enhancing Fast Lithium Ion Conduction in Li4GeO4-Li3PO4 Solid Electrolytes, ACS Appl. Energy Mater., 2, 2019, 6608-6615 Summary of the Invention [Problem to be solved by the invention]
[0006] In Non-Patent Document 1, Li 3.75 Ge 0.75 P 0.25 The paper describes a technique for improving the ionic conductivity of oxide-based solid electrolytes by substituting various cations M for O4. The generalized composition formula is Li 3.75±y (Ge 0.75 P 0.25 ) 1-x M x O4 and Mg 2+ , B 3+ , Al 3+ , Ga 3+ or V 5+ Among them, V 5+ In the system where x was selected, the highest ionic conductivity was observed when x = 0.3, and the conductivity was 5.1 × 10 at 25 °C. -5 It is stated that the viscosity was about S / cm.
[0007] As described above, even the LISICON-type solid electrolyte, which has the highest ionic conductivity reported to date, has an ionic conductivity one to two orders of magnitude lower than that of other oxide-based solid electrolyte materials such as garnet-type materials, and further improvement in ionic conductivity is desired for application to all-solid-state batteries.
[0008] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide an oxide-based solid electrolyte having good ion conductivity, and an all-solid-state lithium ion battery using the same. [Means for solving the problem]
[0009] The present invention, which has been completed based on the above findings, is an embodiment of a compound having the formula: Li α Ge x V y Ti z O4 (wherein, 3.25≦α≦3.8, 0.05≦x≦0.6, 0.25≦y≦0.6, and 0.04≦z≦0.4.) It is an oxide-based solid electrolyte represented by the formula:
[0010] In another embodiment of the oxide-based solid electrolyte of the present invention, in the above formula, 0.25≦x≦0.5.
[0011] In still another embodiment of the oxide-based solid electrolyte of the present invention, in the above formula, 0.30≦y≦0.55.
[0012] In still another embodiment of the oxide-based solid electrolyte of the present invention, in the above formula, 0.045≦z≦0.35.
[0013] In yet another embodiment, the present invention is an all-solid-state lithium ion battery including a solid electrolyte layer formed of an oxide-based solid electrolyte according to an embodiment of the present invention, a positive electrode layer, and a negative electrode layer. Effect of the Invention
[0014] According to the present invention, it is possible to provide an oxide-based solid electrolyte having good ion conductivity, and an all-solid-state lithium ion battery using the same. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a schematic diagram of an all-solid-state lithium-ion battery according to an embodiment of the present invention. [Diagram 2] This is the XRD X-ray diffraction pattern of the base material (Li3.5Ge0.5V0.5O4). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Next, the embodiments of the present invention will be described in detail with reference to the drawings. It should be understood that the present invention is not limited to the following embodiments, and that appropriate changes and improvements in the design may be made based on the ordinary knowledge of those skilled in the art without departing from the spirit of the present invention.
[0017] (Oxide solid electrolyte) The oxide-based solid electrolyte of this embodiment has the composition formula: Li α Ge x V y Ti z O4 (wherein 3.25≦α≦3.8, 0.05≦x≦0.6, 0.25≦y≦0.6, and 0.04≦z≦0.4). The oxide-based solid electrolyte of this embodiment is a LISICON-type solid electrolyte, Li α Ge x V y The composition is obtained by substituting Ti for the O4 base material. With this composition, the number of elements constituting the oxide-based solid electrolyte is increased, and the activation energy is reduced, so that an oxide-based solid electrolyte having good ion conductivity can be obtained. In the present invention, the oxide-based solid electrolyte refers to a solid electrolyte having, in its skeleton, an oxoacid ion in which an oxygen atom is coordinately bonded to a central element, as a counter anion to a lithium ion.
[0018] In the oxide-based solid electrolyte of the present embodiment, if α is less than 3.25 in the composition formula, the carrier concentration is low, so that the ion conductivity may be reduced. If α is more than 3.8, the single-phase synthesis may be difficult. In the oxide-based solid electrolyte of the present embodiment, it is preferable that 3.4≦α≦3.65 in the composition formula.
[0019] In the oxide-based solid electrolyte of the present embodiment, if x is less than 0.05 in the composition formula, there is a risk of a Li4GeO4 phase with low ionic conductivity being generated. If x is more than 0.6, the crystal lattice becomes large, the distance between Li sites becomes long, and there is a risk of a decrease in ionic conductivity. In the oxide-based solid electrolyte of the present embodiment, it is preferable that 0.25≦x≦0.5 in the composition formula.
[0020] In the oxide-based solid electrolyte of the present embodiment, if y is less than 0.25 in the above composition formula, the effect of reducing activation energy by element substitution is weak, so the effect of improving ion conductivity may be small. Also, if y is more than 0.6, impurity phases such as Li4VO4 may be generated, and ion conductivity may decrease. In the oxide-based solid electrolyte of the present embodiment, it is preferable that 0.30≦y≦0.55 in the above composition formula.
[0021] The oxide-based solid electrolyte of this embodiment contains Ti in the above composition formula. The Ti can be substituted for the base material, and has the effect of improving ion conductivity.
[0022] In the oxide-based solid electrolyte of the present embodiment, if z exceeds 0.4 in the above composition formula, an impurity phase such as Li5TiO4 may be generated, and the ion conductivity may decrease. In the oxide-based solid electrolyte of the present embodiment, it is preferable that 0.045≦z≦0.35 in the above composition formula.
[0023] The average particle size of the oxide-based solid electrolyte according to the embodiment of the present invention is not particularly limited, but may be 0.01 to 100 μm, 0.1 to 100 μm, or 0.1 to 50 μm.
[0024] The ionic conductivity of the oxide-based solid electrolyte according to the embodiment of the present invention is 10 -5 S / cm or more is preferable, and 10 -4 More preferably, it is 10 S / cm or more. -3 It is even more preferable that the ionic conductivity is 100 S / cm or more. The ionic conductivity of the oxide-based solid electrolyte can be measured, for example, by the following method. First, 0.2 g of the oxide-based solid electrolyte powder is pressed under a pressure of 550 MPa to form a plate-like provisional shape, and then sintered at 800°C for 12 hours to obtain a molded body. A pellet with a diameter of 10 mm is prepared by applying silver paste to both sides of the molded body. Using the pellet, AC impedance measurement from 20 Hz to 50 MHz is performed at 30°C with an applied voltage of 100 mV. The AC impedance measurement can be performed using E4990A manufactured by Toyo Corporation, which has been subjected to open-short correction. The Li-ion migration resistance is obtained by analyzing the circular arcs seen in the part of the Cole-Cole plot obtained by the AC impedance measurement at frequencies of 30 kHz or more. Next, the ion conductivity is obtained from the Li-ion migration resistance and the thickness and area of the solid electrolyte part of the pellet used for the measurement based on the following formula. Ionic conductivity = Thickness of solid electrolyte part of pellet / [(Li ion migration resistance) × (pellet area)]
[0025] The particles of the oxide-based solid electrolyte of the present embodiment preferably constitute a single phase. With such a structure, there is no phase such as NiO that does not contribute to the movement of Li ions during charging and discharging, and therefore the effect of improving the battery capacity can be expected.
[0026] The oxide-based solid electrolyte particles can be analyzed and identified as being single-phase by a known method based on powder X-ray diffraction. The obtained X-ray diffraction pattern shows that the base material Li 3.5 Ge 0.5 V 0.5 If the X-ray diffraction pattern is identical to that of O4 and no other peaks are observed, it can be determined that the sample is a single phase. Specifically, if the X-ray diffraction pattern shows three diffraction peaks at around 2θ=16°, 28°, and 35°, the sample is determined to be a single phase. The peak at around 2θ=16° corresponds to the diffraction peak of the (200) plane, the peak at around 2θ=28° corresponds to the diffraction peak of the (020) plane, and the peak at around 2θ=35° corresponds to the diffraction peak of the (002) plane.
[0027] (Method of manufacturing oxide-based solid electrolyte) Next, a method for producing an oxide-based solid electrolyte according to an embodiment of the present invention will be described. First, raw materials are weighed out to obtain a desired composition in a glove box filled with an inert gas such as argon gas or nitrogen gas. Examples of the raw materials used here include LiOH·H2O, GeO2, V2O5, TiO2, etc.
[0028] Next, the mixture is mixed in a mortar or the like for 5 to 30 minutes to prepare a mixed powder. At this time, it is preferable to mix for such a time that the average particle size of the mixed powder becomes 5 to 40 μm.
[0029] Next, the mixed powder is placed in an alumina sagger and sintered at 600 to 1000°C for 1 to 20 hours to obtain a powder with the composition formula: Li α Ge x V y Ti z It is possible to prepare an oxide-based solid electrolyte according to an embodiment of the present invention, represented by the formula: O4 (wherein 3.25≦α≦3.8, 0.05≦x≦0.6, 0.25≦y≦0.6, and 0.04≦z≦0.4).
[0030] (All-solid-state lithium-ion battery) A solid electrolyte layer is formed by the oxide-based solid electrolyte according to the embodiment of the present invention, and an all-solid-state lithium ion battery including the solid electrolyte layer, a positive electrode layer, and a negative electrode layer can be produced. The positive electrode layer and the negative electrode layer constituting the all-solid-state lithium ion battery according to the embodiment of the present invention are not particularly limited and can be formed of known materials and can have a known configuration as shown in FIG.
[0031] The positive electrode layer of the lithium ion battery is formed in a layer shape from a positive electrode mixture obtained by mixing a known positive electrode active material for lithium ion batteries with the oxide-based solid electrolyte according to the embodiment of the present invention or another oxide-based solid electrolyte.
[0032] The positive electrode mixture may further include a conductive assistant. As the conductive assistant, a carbon material, a metal material, or a mixture thereof may be used. The conductive assistant may include at least one element selected from the group consisting of, for example, carbon, nickel, copper, aluminum, indium, silver, cobalt, magnesium, lithium, chromium, gold, ruthenium, platinum, beryllium, iridium, molybdenum, niobium, osmium, rhodium, tungsten, and zinc. The conductive assistant is preferably a highly conductive carbon element, a metal element, a mixture, or a compound containing carbon, nickel, copper, silver, cobalt, magnesium, lithium, ruthenium, gold, platinum, niobium, osmium, or rhodium. As the carbon material, for example, carbon black such as Ketjen Black, acetylene black, denka black, thermal black, and channel black, graphite, carbon fiber, activated carbon, and the like may be used.
[0033] The average thickness of the positive electrode layer of the lithium ion battery is not particularly limited and can be appropriately designed depending on the purpose. The average thickness of the positive electrode layer of the lithium ion battery may be, for example, 1 μm to 100 μm, or 1 μm to 10 μm.
[0034] The method for forming the positive electrode layer of the lithium ion battery is not particularly limited and can be appropriately selected depending on the purpose. For example, the method for forming the positive electrode layer of the lithium ion battery includes sputtering using a target material of the positive electrode active material, or compression molding of the positive electrode active material.
[0035] The negative electrode layer of the lithium ion battery may be a layer of a known negative electrode active material for lithium ion batteries, or a layer of a negative electrode mixture obtained by mixing a known negative electrode active material for lithium ion batteries with the oxide-based solid electrolyte according to the embodiment of the present invention or another oxide-based solid electrolyte.
[0036] The negative electrode layer may contain a conductive assistant, as in the positive electrode layer. The conductive assistant may be the same material as that described in the positive electrode layer. As the negative electrode active material, for example, a carbon material, specifically, artificial graphite, graphite carbon fiber, resin-calcined carbon, pyrolytic vapor-grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol resin-calcined carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, non-graphitizable carbon, or a mixture thereof may be used. As the negative electrode material, for example, a metal itself, such as metallic lithium, metallic indium, metallic aluminum, or metallic silicon, or an alloy in combination with other elements or compounds may be used.
[0037] The average thickness of the negative electrode layer of the lithium ion battery is not particularly limited and can be appropriately selected depending on the purpose. The average thickness of the negative electrode layer of the lithium ion battery may be, for example, 1 μm to 100 μm, or 1 μm to 10 μm.
[0038] The method for forming the negative electrode layer of the lithium ion battery is not particularly limited and can be appropriately selected depending on the purpose. Examples of the method for forming the negative electrode layer of the lithium ion battery include sputtering using a target material of the negative electrode active material, compression molding of the negative electrode active material, and vapor deposition of the negative electrode active material.
[0039] The average thickness of the solid electrolyte layer of the lithium ion battery formed by the oxide-based solid electrolyte according to the embodiment of the present invention is not particularly limited and can be appropriately designed according to the purpose. The average thickness of the solid electrolyte layer of the lithium ion battery may be, for example, 50 μm to 500 μm, or 50 μm to 100 μm.
[0040] The method for forming the solid electrolyte layer of the lithium ion battery is not particularly limited and can be appropriately selected depending on the purpose. For example, the method for forming the solid electrolyte layer of the lithium ion battery includes sputtering using a target material of the solid electrolyte, or compression molding of the solid electrolyte.
[0041] Other members constituting the lithium ion battery are not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include a positive electrode collector, a negative electrode collector, and a battery case.
[0042] The size and structure of the positive electrode current collector are not particularly limited and can be appropriately selected depending on the purpose. Examples of the material for the positive electrode current collector include die steel, stainless steel, aluminum, aluminum alloys, titanium alloys, copper, gold, and nickel. The positive electrode current collector may be in the form of, for example, a foil, a plate, or a mesh. The average thickness of the positive electrode current collector may be, for example, 10 μm to 500 μm, or 50 μm to 100 μm.
[0043] The size and structure of the negative electrode current collector are not particularly limited and can be appropriately selected depending on the purpose. Examples of the material for the negative electrode current collector include die steel, gold, indium, nickel, copper, and stainless steel. The negative electrode current collector may be in the form of, for example, a foil, a plate, or a mesh. The average thickness of the negative electrode current collector may be, for example, 10 μm to 500 μm, or 50 μm to 100 μm.
[0044] The battery case is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include known laminate films that can be used in conventional all-solid-state batteries, etc. Examples of the laminate film include a resin laminate film and a film in which a metal is vapor-deposited on a resin laminate film. The shape of the battery is not particularly limited and can be appropriately selected depending on the purpose. Examples of the shape of the battery include cylindrical, square, button, coin, and flat types. EXAMPLES
[0045] The following examples are provided to provide a better understanding of the present invention and its advantages, but the present invention is not limited to these examples.
[0046] Example 1 In a glove box with an argon atmosphere, the raw material composition is Li 3.55 Ge 0.50 V 0.45 Ti 0.05 The raw materials were weighed out and mixed in a mortar for 15 minutes to produce a mixed powder. Next, about 1 g of the mixed powder was placed on an alumina boat and fired at 800 °C for 12 hours to produce Li 3.47 Ge 0.48 V 0.46 Ti 0.049 An oxide-based solid electrolyte having the composition O4 was obtained.
[0047] Example 2 The raw material composition is Li 3.50 Ge 0.45 V 0.50 Ti 0.05 The procedure was carried out in the same manner as in Example 1, except that:
[0048] Example 3 The raw material composition is Li 3.70 Ge 0.50 V 0.30 Ti 0.20 The procedure was carried out in the same manner as in Example 1, except that:
[0049] Example 4 The raw material composition is Li 3.50 Ge 0.30 V 0.50 Ti 0.20 The procedure was carried out in the same manner as in Example 1, except that:
[0050] Example 5 The raw material composition is Li 3.71 Ge 0.33 V 0.33 Ti 0.33 The procedure was carried out in the same manner as in Example 1, except that:
[0051] Example 6 The raw material composition is Li 3.50 Ge 0.10 V 0.50 Ti 0.40 The procedure was carried out in the same manner as in Example 1, except that:
[0052] Example 7 The raw material composition is Li 3.53 Ge 0.48 V 0.48 Ti 0.05 The procedure was carried out in the same manner as in Example 1, except that:
[0053] Example 8 The raw material composition is Li 3.70 Ge 0.60 V 0.30 Ti 0.10 The procedure was carried out in the same manner as in Example 1, except that:
[0054] Example 9 The raw material composition is Li 3.40 Ge 0.30 V 0.60 Ti 0.10 The procedure was carried out in the same manner as in Example 1, except that:
[0055] Comparative Example 1 The raw material composition is Li 3.50 Ge 0.50 V 0.50 The procedure was carried out in the same manner as in Example 1, except that:
[0056] Comparative Example 2 The raw material composition is Li 3.90 Ge 0.50 V 0.10 Ti 0.40 The procedure was carried out in the same manner as in Example 1, except that:
[0057] Comparative Example 3 The raw material composition is Li 3.75 Ge 0.70 V 0.25 Ti 0.05 The procedure was carried out in the same manner as in Example 1, except that:
[0058] Comparative Example 4 The raw material composition is Li 3.85 Ge 0.80 V 0.15 Ti 0.05 The procedure was carried out in the same manner as in Example 1, except that:
[0059] Comparative Example 5 The raw material composition is Li 3.20 Ge 0.15 V 0.80 Ti 0.05 The procedure was carried out in the same manner as in Example 1, except that:
[0060] <Composition analysis> 0.5 g of each oxide-based solid electrolyte sample (powder) obtained in Examples 1 to 9 and Comparative Examples 1 to 5 was weighed out and dissolved in various acids, and then the composition was analyzed using an inductively coupled plasma optical emission spectrometer (ICP-OES) "PS7800" manufactured by Hitachi High-Tech Corporation.
[0061] <Ionic conductivity> 0.2 g of each oxide-based solid electrolyte powder obtained in Examples 1 to 9 and Comparative Examples 1 to 5 was pressed at a pressure of 550 MPa to form a plate-like provisional shape, and then sintered at 800°C for 12 hours to obtain a molded body. A pellet with a diameter of 10 mm was prepared by applying silver paste to both sides of the molded body. Using the pellet, AC impedance measurement from 20 Hz to 50 MHz was performed at 30°C with an applied voltage of 100 mV using an E4990A manufactured by Toyo Corporation, which was subjected to open-short correction. The arcs seen in the frequency portion of the Cole-Cole plot obtained by the AC impedance measurement at 30 kHz or more were analyzed to obtain the migration resistance of Li ions. Next, the ion conductivity was obtained from the migration resistance of Li ions and the thickness and area of the solid electrolyte portion of the pellet used for the measurement based on the following formula. Ionic conductivity = thickness of solid electrolyte part of pellet / [(Li ion migration resistance) × (pellet area)]
[0062] <Single phase> The oxide-based solid electrolyte powders obtained in Examples 1 to 9 and Comparative Examples 1 to 5 were analyzed by powder X-ray diffraction (θ / 2θ method) under the following conditions to determine whether they were single phase. The obtained X-ray diffraction patterns were consistent with those of the base material Li as shown in FIG. 3.5 Ge 0.5 V 0.5 The X-ray diffraction pattern was the same as that of O4, and no other peaks were observed, and it was determined that it was a single phase. Specifically, the X-ray diffraction pattern was determined to be a single phase if the diffraction peaks appeared at three locations, around 2θ=16°, 28°, and 35°. The peak around 2θ=16° corresponds to the diffraction peak of the (200) plane, the peak around 2θ=28° corresponds to the diffraction peak of the (020) plane, and the peak around 2θ=35° corresponds to the diffraction peak of the (002) plane. In Table 1, the samples that were a single phase are marked as "A", and those that were not a single phase are marked as "B". X-ray diffraction equipment: Rigaku SmartLab ·Light source: CuKα line Voltage: 40kV ·Current: 30mA The above manufacturing conditions and test results are shown in Table 1.
[0063] [Table 1]
[0064] (Evaluation Results) The oxide-based solid electrolytes of Examples 1 to 9 all have the composition formula: Li α Ge x V y Ti z O4 (wherein 3.25≦α≦3.8, 0.05≦x≦0.6, 0.25≦y≦0.6, and 0.04≦z≦0.4), whereas Comparative Examples 1 to 5 did not have this composition. Therefore, the oxide-based solid electrolytes according to Examples 1 to 9 had better ion conductivity than those not having the above composition in Comparative Examples 1 to 5. Therefore, it is expected that the battery capacity of the all-solid-state lithium ion battery using the solid electrolytes according to Examples 1 to 9 will be improved.
Claims
1. Composition formula: Li α Ge x V y Ti z O 4 (In the formula, 3.25≦α≦3.8, 0.05≦x≦0.6, 0.25≦y≦0.6, and 0.04≦z≦0.4.) An oxide-based solid electrolyte represented by the formula:
2. 2. The oxide-based solid electrolyte according to claim 1, wherein, in the formula, 0.25≦x≦0.
5.
3. 3. The oxide-based solid electrolyte according to claim 1, wherein y satisfies the formula: 0.30≦y≦0.
55.
4. The oxide-based solid electrolyte according to any one of claims 1 to 3, wherein, in the formula, 0.045≦z≦0.
35.
5. An all-solid-state lithium ion battery comprising a solid electrolyte layer made of the oxide-based solid electrolyte according to any one of claims 1 to 4, a positive electrode layer, and a negative electrode layer.
Citation Information
Patent Citations
Solid state electrochemical cell including lithium iodide as an electrolyte additive
US5458995A
Solid electrolyte composition, electrode sheet for all-solid-state secondary battery, all-solid-state secondary battery, and method for producing electrode sheet for all-solid-state secondary battery and all-solid-state secondary battery
WO2017204027A1
Solid-state battery
WO2021145312A1